A study of magnetic resonance imaging-derived cervical spinal cord dimensions in young adult Nigerians: Clinical relevance (Journal of Experimental and Clinical Anatomy, 2019)
INTRODUCTION: Knowledge of cervical cord dimensions is important in making diagnosis of pathological conditions of the spinal cord. This study used magnetic resonance imaging to determine the normal dimensions of the cervical spinal cord in young adult Nigerians and the influence of age and sex on these dimensions.METHODS: A prospective study of 100 healthy asymptomatic individuals (50 males and 50 females) aged 21–40 years was carried out at Memfys Hospital, Enugu, Nigeria. Disc‑level axial T1‑weighted 0.35T magnetic resonance images of anteroposterior dimensions (APDs) and transverse dimensions (TDs) were obtained from C2/C3 to C7/T1 in millimeters. Approximate cord area (ACA) was calculated as the product of APD and TD. Test of significance for age‑ and sex‑adjusted dimensions was determined.RESULTS: TD increased from C2/3 (12.2 ± 1.0 mm) to peak at C5/6 level (13.4 ± 1.2 mm) before dropping to 11.6 ± 1.4 mm (C7/T1). APD decreased from 8.1 ± 0.6 mm (C2/3) to 6.9 ± 0.7 mm (C7/T1). ACA also increased from 98.7 ± 11.7 mm2 (C2/3) to peak value of 103.3 ± 14.6 mm2 (C5/6), but dropped to 80.0 ± 14.3 mm2 (C7/T1). In general, there was no significant gender‑based difference in values of the cord dimensions except in TD at C2/3 (0.036). ANOVA revealed a significant difference in age‑adjusted values of TD (0.022) and AP (0.042) at C5/6. Only TD values had significant variability at C5/6 level when individuals in the age group of 36–40 years were compared to those <30 years old.CONCLUSION: TD and ACA give more representative values of cervical spinal cord size and should be utilized clinically in the assessment of these dimensions. The C5/6 has the highest cervical spinal cord dimension. Sex‑adjusted dimensions generally did not show statistically significant difference. There is subtle but significant reduction in TD of cervical spinal cord at C5/6 level toward the age of 40 years.